How can heat stress affect chicken meat quality? – a review. (31st August 2018) - Zaboli, Gholamreza; Huang, Xi; Feng, Xi; Ahn, Dong U
ABSTRACT: Heat stress is one of the most important environmental stressors for the poultry industry in the world. Reduced growth rate, low feed efficiency, impaired immunological responses, changes in intestinal microflora, and deterioration of meat quality are the consequences of acute or chronic heat stress. In terms of meat quality, 3 primary mechanisms have been suggested to explain this phenomenon: 1) rapid drop in pH during and after slaughter due to the glycogen conversion to increase in lactic acid accumulation especially when the muscle temperature is high, a combination of high temperature and low pH that facilitates the denaturation of sarcoplasmic proteins resulting in lower water-holding capacity of muscle; 2) acceleration of panting to dissipate body heat, which increases CO2 exhalation and pH drop in blood, initiates metabolic acidosis in skeletal muscle. Increase in panting is also associated with a high release of corticosteroid hormones; 3) the reactive oxygen species produced by heat stress increases the oxidative stress in the birds, which can damage the structure and functions of the enzymes that regulate sarcoplasmic calcium levels in muscles. Overall, these changes in the muscle cells accentuate energy expenditure due to constant muscle contractions. This review discusses the scientific evidence about how heat stress affects the quality of chicken meat through the acid/base status, oxidative reactions, and changes in hormonal secretions.